The establishment of National Air Quality Health Index in China. (May 2020) - Du, Xihao; Chen, Renjie; Meng, Xia; Liu, Cong; Niu, Yue; Wang, Weidong; Li, Shanqun; Kan, Haidong; Zhou, Maigeng
Highlights: We established AQHIs for various subgroups using data from 272 Chinese cities. Various AQHIs showed very similar magnitude for the associations with mortality. The associations of AQHI with mortality were one-half to -fold stronger than AQI. The curves for AQHI and mortality were consistently increasing but not for AQI. Abstract: Background: A new Air Quality Health Index (AQHI) was developed in Canada or several single cities as a promising health risk communication tool. Objectives: To construct a national AQHI in China and compare its validity in predicting daily mortality risk with the existing Air Quality Index (AQI). Methods: We established the AQHI as the sum of excess total mortality risks associated with multiple air pollutants in 272 representative Chinese cities from 2013 to 2015 (termed as "total AQHI"). The mortality risks per unit change of air pollutant concentrations were determined according to a time-series analysis in each city. Separate AQHIs were established for subgroups classified by age and sex and for main cardiopulmonary diseases (termed as "specific AQHIs"). For validation, AQHIs and AQI were established using the data of 2015 (N = 272) and compared their associations with daily mortality using the data of 2013–2014 (N = 144). Results: The concentration-response coefficients of fine particulate matter, nitrogen dioxide and ozone were adopted in constructing AQHI. There were almost linear exposure-response relationships between AQHIs and daily mortality. The total AQHI and specific AQHIs had very similar associations with daily mortality. AQHI and AQI showed similar associations with daily cause-specific mortality in terms of average magnitude, numbers of cities of positive associations and model fit statistics. Conclusions: AQHI may have comparable performance with AQI in communicating acute health risks of air pollution in China. There seems no need to establish specific AQHIs for different age groups, gender and causes of deaths.